A paradigm shift framed by a crisis - Jalušič, Vlasta (Annales. Series historia et sociologia, 2020)
The article examines recent public debates on migration and integration in Austria, Denmark, Poland, Slovenia, Spain, and the UK. Shifts in public opinion relate to the 2015 mass migration termed as a crisis, while recent years have seen a substantial move of immigration policy and public debates from proclamations of democratic values towards a recently much harsher approach to immigration and integration. We argue that a gap exists between public opinion, policies, and discourses formulated at the EU and national levels. This gap might indicate that it is not the public opinion which influences public policies but rather the established legal and policy "crisis" frameworks, coupled with media landscapes that considerably affect the majority's perception of immigrants' rights and their prospects for integration.
Keywords: comunita di accoglienza; crisi; crisis; integracija; integration; integrazione; javno mnenje; kriza; media representations; medijske reprezentacije; opinione pubblica e atteggiamenti; public opinion and attitudes; rappresentazioni dei media; reception communities; sprejemne skupnosti